Antimicrobial Resistance and Genotype Characteristics of Vibrio scophthalmi Isolated from Diseased Mariculture Fish Intestines With Typical Inter-Annual Variability - Yu, Yongxiang; Liu, Xiao; Wang, Yingeng; Liao, Meijie; Tang, Miaomiao; Rong, Xiaojun; Wang, Chunyuan; Li, Bin; Zhang, Zheng (Frontiers in Marine Science, 2022)
As an intestinal organism settled long-term within the gut of marine fish, Vibrio scophthalmi is a potential object for the bacterium genetic variation and adaptation research. The genetic diversity, antimicrobial resistance phenotype, and genotype of 33 V. scophthalmi isolated from diseased marine fish intestines between 2002 and 2020 were evaluated. The results showed that all isolates were frequently resistant to penicillins, cephalosporins, aminoglycosides, and macrolides and displayed multidrug-resistant (MDR) phenotype in vitro. Thirty percent of isolates were resistant to more than 20 different drugs. The average insensitive (resistant and intermediate) rate of V. scophthalmi isolates was 49.5% 81.8% between 2002 and 2020, but the t-test revealed that there was no significant difference in the drug-resistance rate of V. scophthalmi isolates with typical interannual variability. Eleven antimicrobial resistance genes (strB, strA, ant(3 ˝)-I, mphA, blaPSE, qnrS, tetC, tetE, tetM, tetS, and int1) were detected in these isolates, but the antimicrobial resistance phenotypes and genotypes of these isolates were not consistent. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) analysis indicated that 33 isolates could be divided into two clusters (G1 and G3) and two single isolates (G2 and G4), and the G2 cluster was isolated from South Sea C. undulates with typical geographical species differences. There was no significant correlation between the drug susceptibility and the genetic types of V. scophthalmi isolates. The results reveal the mismatch phenomenon between antimicrobial resistance and genotype of inherent V. scophthalmi in the marine fish intestines, and the antimicrobial susceptibility isolates might be a potential risk source for storage and transmission of resistance genes.